Managing Complexity in Activity Specifications by Separation of Concerns and Reusability - Peter Forbrig; Gregor Buchholz (Complex Systems Informatics and Modeling Quarterly)
The specification of activities of the different stakeholders is an important activity for software development. Currently, a lot of specification languages like task models, activity diagrams, state charts, and business specifications are used to document the results of the analysis of the domain in most projects. The paper discusses the aspect of reusability by considering generic submodels. This approach increases the quality of models. Additionally, the separation of concerns of cooperation and individual work by subject-oriented specifications is discussed. It will be demonstrated how task models can be used to support subject-oriented specification by so called team models and role models in a more precise way than S-BPM specifications. More precise restrictions on instances of roles can be specified.